The family business 5 - Weber, Carl, 1964-; Weber, Carl, 1964-; Hunt, La Jill (Weber, Carl, 1964- Family business novel., 2020)
From the time he was a boy in Georgia, LC Duncan, patriarch and leader of the Duncan clan, has battled racism. Even now that he and his family are truly successful, the racism can still be in-your-face. Maybe it<U+2019>s the political climate or perhaps it<U+2019>s just bad timing, but LC and the rest of the Duncans are being challenged by the ultimate power-hungry racist, Sheriff KD Shrugs. Nevada Duncan is at that age when girls and sex are always on his mind. His handsome face and superior intellect attract Kia, the beautiful “Blasian” call girl who tempts him into running away to a place where the Duncans are definitely not wanted<U+2014>El Paso, Texas, the home of KD Shrugs. What is the worst thing that can happen to a handsome, rich millennial? Rio Duncan would say it<U+2019>s mistaken identity after being beat down in a nightclub by someone who thinks he<U+2019>s Roman Johnson, a stickup kid who happens to be Rio<U+2019>s doppelganger. What happens next will open up the biggest can of worms the Duncans have ever had to deal with.